Ultrashort Broadband Cooperative Pulses for Multidimensional Biomolecular NMR Experiments. Issue 44 (25th April 2018) - Asami, Sam; Kallies, Wolfgang; Günther, Johannes C.; Stavropoulou, Maria; Glaser, Steffen J.; Sattler, Michael
Abstract: NMR spectroscopy at ultra‐high magnetic fields requires improved radiofrequency ( rf ) pulses to cover the increased spectral bandwidth. Optimized 90° pulse pairs were introduced as Ramsey‐type cooperative (Ram‐COOP) pulses for biomolecular NMR applications. The Ram‐COOP element provides broadband excitation with enhanced sensitivity and reduced artifacts even at magnetic fields >1.0 GHz 1 H Larmor frequency (23 T). A pair of 30 μs Ram‐COOP pulses achieves an excitation bandwidth of 100 kHz with a maximum rf field of 20 kHz, more than three‐fold improved compared to excitation by rectangular pulses. Ram‐COOP pulses exhibit little offset‐dependent phase errors and are robust to rf inhomogeneity. The performance of the Ram‐COOP element is experimentally confirmed with heteronuclear multidimensional NMR experiments, applied to proteins and nucleic acids. Ram‐COOP provides broadband excitation at low rf field strength suitable for application at current magnetic fields and beyond 23 T. Abstract : Ultra‐highfield NMR magnet development requires robust radio frequency pulses to cover the increasing frequency spectral bandwidth. Cooperative excitation pulses are presented with pulse durations on the order of tens of microseconds, which provide ultrabroadband excitation for present and future magnetic field strengths well beyond 28 T (1.2 GHz 1 H). The performance is demonstrated for proteins and nucleic acids.